Social Mapping in Nursing Education- Steps and Implication - Silpa Chintham; Sirshendu Chaudhuri; Jayanthi Tarugu; Kiranmayi Koni (Medsci Publications, 2022)
Background: Social mapping, though an old approach in public health education and research, not practiced much in nursing education. This study was conducted to describe the social mapping process in a semi-urban area in the Chittoor district of Andhra Pradesh in India and to describe the implications of such social mapping from the students' perspective. Methods: This participatory rural appraisal was conducted for the Bachelor of Nursing Students in a semi-urban settlement in the state of Andhra Pradesh in India. The social mapping process was conducted in three broad steps- classroom-based teaching of social mapping, conducting social mapping in the community and a debriefing session with the students. The major outcome of this educational activity was the social map. In addition, we also came up with the students' implications through group discussion. Results: A facility map was constructed by the community members which was replicated by the teachers. The map was triangulated by the teachers through a transect walk in that area. The students came out with various academic, clinical, and administrative implications from this educational session. Conclusion: Social mapping can be used as a potential tool in nursing education. More evidence is required on this learning approach before recommending it in the Community Nursing curriculum.